Neurological and Biological Foundations of Children's Social and Emotional Development: An Integrated Literature Review - Nelson, Helen; Kendall, Garth; Shields, Linda (SAGE Publishing, 2013)
This article provides an integrated review of the expert literature on developmental processes that combine social, biological, and neurological pathways, and the mechanisms through which these pathways may influence school success and health. It begins with a historical overview of the current understanding of how attachment relationships and social environments influence brain development and plasticity and are, therefore, central to the physical and mental health of individuals and populations. It then expands on the effect of plasticity in relation to behavior and learning at school. This article concludes with a discussion of the role the school nurse may play in supporting health and learning by recognizing signs of relational stress and by advocating for prevention strategies.